Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening - Ayunda, Risma Berliana; Kassmawati, Yuni (YUME : Journal of Management, 2025)
This study is to examine the effect of competence and work discipline on work motivation with work motivation as an intervening variable. This study was conducted at Telkom Witel North Jakarta Jakarta which is a branch office of the telecommunications business area. This research is quantitative research with data analysis using Structural Equation Modeling- Partial Least Square (SEM-PLS). The study population consisted of 100 sales employees and all existing pupolations were sampled. The results showed that Competence, Work Discipline had a positive and significant effect on Employee Performance at PT Telkom Indonesia (Persero) Tbk (Telkom) Telkom Witel North Jakarta branch. Work Motivation has a positive and significant effect on Employee Performance at PT Telkom Indonesia (Persero) Tbk (Telkom) North Jakarta Telkom Witel branch. While Competence has no significant effect on Employee Performance through Work Motivation at PT Telkom Indonesia (Persero) Tbk (Telkom) North Jakarta Telkom Witel branch. Work Discipline has a significant effect on Employee Performance through Work Motivation at PT Telkom Indonesia (Persero) Tbk (Telkom) North Jakarta Witel Telkom branch.Keywords: Competence, Work Discipline, Work Motivation, Employee Performance